Routine screening for iron deficiency is an important component of athlete care - Chapman, R. F.; Sinex, J.; Wilber, R.; Kendig, A.; Moreau, B.; Nabhan, D.; Stray-Gundersen, J. (Medicine & Science in Sports & Exercise, 2017)
Letter to the editor concerning Parks RB, Hetzel SJ, Brooks MA. Iron deficiency and anemia among collegiate athletes: a retrospective chart review. Med Sci Sports Exerc. 2017;49(8):1711-5